The integrated usage of ground-based and satellite SAR, along with 3D structural modelling in Titania: creating a link between short and long - term slope stability hazard management. Issue 1 (August 2021) - Botsialas, K; Ravde, V; Falomi, A; Meloni, F; Boldrini, N; Bellotti, F; Leoni, L; Coli, N
Abstract: Mining is a high risk business and for every modern mining industry, the main aim of its open pit design is to create walls that will be stable for the life of the open pit, which in some cases may extend beyond the closure. As a result, any kind of instability should be manageable and if possible, it should not develop to instabilities. This paper focuses on 300.000 tons instability that began in 2008 and continues until today in Titania. The hazard associated with this instability was a constant threat for the continuation of the production and the safety of people and machinery. In order to manage the hazard in short- and long-term, it was evident that data from different sources should be combined and analyzed. Data from ground-based and satellite SAR were used to delineate the unstable area through a period of 10 years. At the same time advanced implicit modelling techniques were used to integrate borehole and surface structural data in a 3D structural model. This 2 stage workflow, led to a set of preventive and remedial measures that allowed the continuation of the production the last ten years and will ensure the continuation of the production for, at least, other ten years.